Analysis of the contribution of IFRS to improving the relevance of financial performance measures: A comparative study with Moroccan Accounting Standards - Adil Laouane; Mohamed Torra (Investment Management & Financial Innovations, 2023)
The implementation of the international accounting framework has led to a new philosophy of estimating and valuing the financial performance of companies. In this respect, the accounting indicators derived from financial statements constitute the classic measures of performance evaluation, such as ROE, ROA, BPA, and Payout. However, their usefulness is contested in the face of market-based indicators like TSR, MVA, PBR, and dividend yield. This paper aims to assess the effect of adopting IFRS on the relevance of financial performance measures through a comparative approach with Moroccan GAAP. At the empirical level, the use of multiple regressions on panel data remains strongly solicited to test the informational relevance of these indicators. In number, there are 115 observations collected from IFRS-adopting companies and 418 observations from non-adopting companies over the period 2013–2022. The study revealed a significant impact of the adoption of IFRS on the informational relevance of accounting indicators (adjusted R2(IFRS) = 71.12% against adjusted R2(Moroccan GAAP) = 55.03%). However, this study found a less significant effect of IFRS on the degree of relevance of stock market performance indicators (adjusted R2 (IFRS) = 50.36% versus adjusted R2(Moroccan GAAP) = 63.84 %). The study also showed a significant effect of IFRS on the complementarity between accounting and stock market performance indicators to explain the total shareholder return (adjusted R2(IFRS) = 69.02% against adjusted R2(Moroccan GAAP) = 58.01%).